2015
DOI: 10.1111/1365-2435.12452
|View full text |Cite
|
Sign up to set email alerts
|

Drought tolerance as predicted by leaf water potential at turgor loss point varies strongly across species within an Amazonian forest

Abstract: 1.Amazonian droughts are predicted to become increasingly frequent and intense, and the vulnerability of Amazonian trees has become increasingly documented. However, little is known about the physiological mechanisms and the diversity of drought tolerance of tropical trees due to the lack of quantitative measurements. 2.Leaf water potential at wilting or turgor loss point (π tlp ) is a determinant of the tolerance of leaves to drought stress, and contributes to plant-level physiological drought tolerance. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
181
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(203 citation statements)
references
References 106 publications
(242 reference statements)
19
181
1
2
Order By: Relevance
“…The osmotic potential at full turgor (Ψ π(100) ) was significantly lower in the forest species (FS) F. mathewsii and the pioneer species (PS) C. lanata compared to O. vervesinoides (PS) and C. xanthochloros (FS). Leaf Ψ π(100) and Ψ π(0) have been highly correlated in a number of studies [22]. Thus, it is consistent that the osmotic potential at zero turgor (Ψ π(0) ) showed a similar pattern, with the highest values found in O. vervesinoides and C. xanthochloros ( Table 2).…”
Section: Resultssupporting
confidence: 67%
“…The osmotic potential at full turgor (Ψ π(100) ) was significantly lower in the forest species (FS) F. mathewsii and the pioneer species (PS) C. lanata compared to O. vervesinoides (PS) and C. xanthochloros (FS). Leaf Ψ π(100) and Ψ π(0) have been highly correlated in a number of studies [22]. Thus, it is consistent that the osmotic potential at zero turgor (Ψ π(0) ) showed a similar pattern, with the highest values found in O. vervesinoides and C. xanthochloros ( Table 2).…”
Section: Resultssupporting
confidence: 67%
“…This kind of information, as provided in our study, may be useful for more accurate calibration of models of global vegetation dynamics at the regional scale, and better estimates when applied on wider scales. Finally, several ecophysiological studies have indicated that the regulation of phenological events of tropical trees is species-specific [71]. Accordingly, our results may in part represent spurious associations with non-causal variables, in spite of the fit of the data to our models.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, genotypes within populations and species or functional groups within the community with differential sensitivities to a particular climate extreme presents a mechanistic pathway for directional changes to plant community diversity, composition and likely productivity. Plant species in both forest and herbaceous ecosystems possess high variation in their physiological stress tolerances [9,35,36]. As a result, there is evidence of differential sensitivity among plant genotypes [37,38], species [9,[39][40][41] and functional groups [4,42,43] to climate extremes.…”
Section: Scaling Individual Plant Responses To the Population And Commentioning
confidence: 99%